Role of NADPH Oxidase-4 in Human Endothelial Progenitor Cells - Hakami, Nora Y.; Ranjan, Amaresh K.; Hardikar, Anandwardhan A.; Dusting, Greg J.; Peshavariya, Hitesh M. (Frontiers in Physiology, 2017)
Introduction: Endothelial progenitor cells (EPCs) display a unique ability to promote angiogenesis and restore endothelial function in injured blood vessels. NADPH oxidase 4 (NOX4)-derived hydrogen peroxide (H2O2) serves as a signalling molecule and promotes endothelial cell proliferation and migration as well as protecting against cell death. However, the role of NOX4 in EPC function is not completely understood. Methods: EPCs were isolated from human saphenous vein and mammary artery discarded during bypass surgery. NOX4 gene and protein expression in EPCs were measured by real time-PCR and Western blot analysis respectively. NOX4 gene expression was inhibited using an adenoviral vector expressing human NOX4 shRNA (Ad-NOX4i). H2O2 production was measured by Amplex red assay. EPC migration was evaluated using a transwell migration assay. EPC proliferation and viability were measured using trypan blue counts. Results: Inhibition of NOX4 using Ad-NOX4i reduced Nox4 gene and protein expression as well as H2O2 formation in EPCs. Inhibition of NOX4-derived H2O2 decreased both proliferation and migration of EPCs. Interestingly, pro-inflammatory cytokine tumour necrosis factor alpha (TNFα) decreased NOX4 expression and reduced survival of EPCs. However, the survival of EPCs was further diminished by TNF-α in NOX4-knockdown cells, suggesting that NOX4 has a protective role in EPCs. Conclusion: These findings suggest that NOX4-type NADPH oxidase is important for proliferation and migration functions of EPCs and protects against pro-inflammatory cytokine induced EPC death. These properties of NOX4 may facilitate the efficient function of EPCs which is vital for successful neovascularization.